2021
DOI: 10.3389/feduc.2021.647626
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on Research Postgraduate Students’ Understanding of Academic Integrity at a Hong Kong University

Abstract: This case study aims to understand how research postgraduate (RPg) students at a Hong Kong university perceive academic integrity before and after participating in the Trail of Integrity and Ethics on the general issues of academic misconduct (TIE-General learning trail), which makes use of Augmented Reality (AR) technology and mobile application to help students acquire abstract concepts (Wong et al., 2018). A total of 33 RPg students, who had completed the mandatory courses on research ethics and teaching sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Second, we examined the relationship between mindfulness and academic dishonesty (H 4 ). The results, in line with previous literature (De Maio & Dixon 2022;Lau 2021), confirm that mindfulness negatively correlates to academic dishonesty. This result may be due to mindfulness' implicit characteristics as a (un)ethical behaviour regulator (Paruzel-Czachura & Kocur 2023; Y.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Second, we examined the relationship between mindfulness and academic dishonesty (H 4 ). The results, in line with previous literature (De Maio & Dixon 2022;Lau 2021), confirm that mindfulness negatively correlates to academic dishonesty. This result may be due to mindfulness' implicit characteristics as a (un)ethical behaviour regulator (Paruzel-Czachura & Kocur 2023; Y.…”
Section: Discussionsupporting
confidence: 92%
“…On the one hand, the research found a relationship between dishonest behaviour and statistics anxiety (Eshet et al 2021Steinberger et al 2021). On the other hand, mindfulness is negatively related to academic dishonesty (Culiberg & Mihelič, 2020;De Maio & Dixon 2022;Lau 2021). Thus, based on the above, we posit: H 5 : Mindfulness will mediate the relationship between statistics anxiety and academic dishonesty.…”
Section: Mindfulness Academic Dishonesty and Statistics Anxietymentioning
confidence: 99%